Basic Level Student Management Leadership Training (LKMM) Fostering Leadership Spirit in the Creative, Innovative, and Loyal Millennial Generation in Society 5.0 - Inoki Ulma Tiara (Universitas PGRI Sumatera Barat, 2023)
Leadership is not a rigid concept that can be learned solely from textbooks, but rather, it is a fusion of theory and practice. Therefore, to enhance the fundamental capabilities of student organizations, a training program titled 'Basic Level Student Management Leadership Training (SMLT) to Cultivate Leadership Spirit in the Creative, Innovative, and Loyal Millennial Society 5.0' is required.